PENERAPAN MEDIA GAMBAR DALAM UPAYA MENINGKATKAN KEMAMPUAN MENULIS PANTUN SISWA KELAS IV SD INPRES KALUKUBULA - Masni, Masni (BAHASANTODEA, 2016)
There is the objective of this research is to describe the steps of writing a pantun with using picture media of the fourth grade students at SD Inpres Kalukubula. Kind of this research is a classroom action research which adopted by Kurt Lewin Model which developed by Kemmis and Mc. Taggart, it is include 4 steps, (a) planning, (b) Implementing, (c) Observation, and (d) reflection. There are four aspects of writing pantun assesment, hey are, (1) Theme, (2) diction, (3)sampiran and (4) content. The application of learning writing pantun with using picture media is done with identification step of things which it exist at the picture, choosing a words which based on the picture, and arrange the words to be sentences of pantun. The result of analysis at the cycle I that there are six students from the total of the students is 21 students which achieve the individual learning completeness. Individual learning of completeness which decided in the SD Inpres Kalukubula at the indonesian language subject is 70. The table above show that the sum of the students which had the learning completeness is 6 students. It is that the individual learning completeness achieve 28,5%. Whereas the students which not yet achieve learning completeness is 15 students (71,42%). There is the result of analysis at the cycle II that completeness of achievement learning result of the students at the writing pantun learning with using picture media in the cycle II had achieve classical mnimal completeness criteria, it is 90%. Therefore, it can be concluded learning ofÂ  writing pantun with using picture media at the cycle II had succes to improve the students ability in writing pantun.